2004
DOI: 10.1007/s10340-003-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Soaking faba bean seed in some bio-agents as prophylactic treatment for controlling Meloidogyne incognita root-knot nematode infection

Abstract: Soaking faba beans or treating their soil with the bio-agents Abamectin (a fermentation product from Streptomyces avermitilis), a strain of Bacillus thuringiensis, Nemaless (containing strains of Serratia marcescens), and Sincocin-AG were compared to the nematicide Oxamyl and significantly (P £ 0.01 and/or P £ 0.05) reduced the population density of M. incognita with increasing the measured plant growth . On this basis, seed soaking was recommended as an economical, easy and pollution free method for managing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…These results agree with those obtained by Garabedian and Van Gundy (1983); Blackburn et al (1996); Auarles (1991);El-Nagdi and Youssef (2004) and Lashein (2002). The reduction in M. incognita parameters may be referred to gross effect of abamectin on the movement and infective behavior of the parasites.…”
Section: Discussionsupporting
confidence: 83%
“…These results agree with those obtained by Garabedian and Van Gundy (1983); Blackburn et al (1996); Auarles (1991);El-Nagdi and Youssef (2004) and Lashein (2002). The reduction in M. incognita parameters may be referred to gross effect of abamectin on the movement and infective behavior of the parasites.…”
Section: Discussionsupporting
confidence: 83%
“…Rhizobacteria reduce nematode populations mainly by production of toxins (Siddiqui and Mahmood, 1999), induction of systemic resistance (Hasky-Gunther et al, 1998), changing nematode behavior (Sikora and Hoffmann-Hergarter, 1993) and interfering with plant recognition (Oostendorp and Sikora,1990) and promoting plant growth (El-Nagdi and Youssef, 2004). A commercial transplant mix (Bio yield TM , Gustafson LLC) containing Paenobacillus macerans and Bacillus amylolique faciens has been developed to control plant parasitic nematodes on tomato, bell pepper and straw berry in USA (Meyer, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Natural products from actinomycetes, especially Streptomyces spp., are a very promising source of new chemicals to manage plant-parasitic nematodes (Chubachi et al 1999; Dong and Zhang 2006; El-Nagdi and Youssef 2004; McGovern et al 2002; Samac and Kindel 2001;). Fervenulin ( 1 ), known also as planomycin, is a yellow crystalline solid, which was previously isolated from S. fervens and S. rubrireticuli (Liao et al 1965).…”
Section: Discussionmentioning
confidence: 99%
“…are the major group of actinomycetes which show activity against plant-parasitic nematodes by producing nematicidal metabolites (Dicklow et al 1993; Mishra et al 1987; Samac and Kindel 2001; Sun et al 2006). According to El-Nagdi and Youssef (2004), abamectin, a member of the avermectin group obtained from the fermentation products of Streptomyces avermitilis , showed nematicidal activity by the seed soaking treatment of faba beans infested with M. incognita . Moreover, it was found that the mortality of M. incognita and Rotylenchulus reniformis reached 100 and 97% respectively, after 24 h exposure to 21.5 μg abamecin/ml (Faske and Starr 2006).…”
Section: Introductionmentioning
confidence: 99%